Emergence and Genomic Characterization of a KPC-2-, NDM-1-, and IMP-4-Producing Klebsiella michiganensis Isolate - Yanyan Zhang; Danxia Gu; Xuemei Yang; Yuchen Wu; Congcong Liu; Zhangqi Shen; Rong Zhang (Frontiers in Microbiology, 2022)
A rectal swab sample was collected from a patient with Guillain–Barré syndrome and enriched in lysogeny broth. Carbapenem-resistant bacteria were selected by China Blue agar plates containing 0.3 μg/ml meropenem. Carbapenemase-producing Klebsiella michiganensis was identified and characterized by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF), immune colloidal gold technique, a conjugation experiment, PCR analysis, and antimicrobial susceptibility testing. The genome of K. michiganensis was determined by whole genome sequencing. Antimicrobial susceptibility testing showed that the K. michiganensis was resistant to imipenem, meropenem, ertapenem, cefmetazole, ceftazidime, cefotaxime, piperacillin/tazobactam, sulbactam/cefoperazone, ceftazidime/avibactam, cefepime, and aztreonam while susceptible to polymyxin B, ciprofloxacin, tigecycline, and amikacin. Immune colloidal gold technique suggested that this strain co-produced three different carbapenemases [Klebsiella pneumoniae carbapenemase (KPC), New Delhi metallo-beta-lactamase (NDM), and Imipenem (IMP)]. Whole genome sequencing analysis indicated that this strain belonged to ST91, and blaKPC–2, blaNDM–1, and blaIMP–4 were carried on different conjugative plasmids. Besides, the co-existence and transferability of blaKPC–2, blaNDM–1, and blaIMP–4 in K. michiganensis facilitates the potential horizontal dissemination and nosocomial spread of resistance genes among multidrug-resistant organisms.